PERBANDINGAN NILAI EKONOMI POHON ANTARA METODE ISTEM DAN THYER - Arbian, Yeli; Sutrisno, Alfred Jansen (Jurnal Hutan Tropis, 2025)
The economic value of trees is important because trees produce wood that has a selling value with a market price approach. This study aims to compare the economic value of trees between the ISTEM and Thyer methods on the UKSW Diponegoro campus. These methods show their interdependence on the economic aspect, which is found in the two estimation methods and the aesthetic aspect found in the ISTEM method. The benefits of this research provide information about the economic value of trees with ISTEM and Thyer estimation models on landscape trees. The analysis used to determine the comparison of the economic value of trees using the ISTEM and Thyer methods. The results showed an assessment of the economic value of UKSW Diponegoro campus trees, namely ISTEM and Thyer. The highest economic value on Mahogany trees, the ISTEM method produces Rp. 206,412,236.13, while the Thyer method provides a lower value of Rp. 199,788,992.59 found significant variations in economic value between trees. In Kesumba trees, the ISTEM method gave the lowest value of Rp. 827,839.44, while the Thyer method gave a much higher economic value of Rp. 19,279,451.33. In Thyer's method with the lowest economic value tree on the pulai tree of Rp. 14,841,037.06 compared to the Pulai tree using the ISTEM method, the economic value is lower at Rp. 7,279,190.69. This difference shows a significant difference in value assessment between the two methods, this is due to the parameters used. The ISTEM method shows differences in economic value between trees, influenced by factors such as tree height, trunk diameter, wood quality, and growth rate.